2017
DOI: 10.21767/2471-8521.100020
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus Disseminated Infection in Paediatric Acute Lymphoblastic Leukaemia: A Case Report

Abstract: Here we report the case of a disseminated Aspergillus flavus infection in an adolescent affected by acute lymphoblastic leukaemia at the beginning of first-line chemotherapy. Association of surgery and combination antifungal therapy (high dose liposomal amphotericin B and caspofungin) allowed infection improvement. 18-FDG PET-MRI was used for response-to therapy monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Many supportive studies have shown that A. flavus to be sensitive to voriconazole, like Denardi et al and Mahdavi-Omran et al which have reported MIC GM values 0.871 and 0.27 µg/ml respectively (7,11). Moreover, in a study by Borman et al only 0.7% of A. flavus isolates were resistant to voriconazole (10) whereas all tested isolates by Varotto et al were sensitive to voriconazole (35).…”
Section: Discussionmentioning
confidence: 96%
“…Many supportive studies have shown that A. flavus to be sensitive to voriconazole, like Denardi et al and Mahdavi-Omran et al which have reported MIC GM values 0.871 and 0.27 µg/ml respectively (7,11). Moreover, in a study by Borman et al only 0.7% of A. flavus isolates were resistant to voriconazole (10) whereas all tested isolates by Varotto et al were sensitive to voriconazole (35).…”
Section: Discussionmentioning
confidence: 96%